Sustainable development of a carob-based food with antioxidant and prebiotic functionality via in situ enzymatic and microbial fructo-oligosaccharide production - Amoedo, Sofia Mendes (2025)
Fructo-oligosaccharides (FOS) are well-established prebiotics, while polyphenols have recently demonstrated their potential as prebiotics. Carob pulp, with its high intrinsic sucrose content and high levels of polyphenols, shows great potential to be transformed into a prebiotic food. In this study, we investigated the development of a functional food product based on carob pulp, with an emphasis on sustainability. The intrinsic sucrose content of the carob pulp extracts was in situ converted into the prebiotic FOS using two approaches: 1) commercial enzyme complexes, specifically, Viscozyme® L, Pectinex® Ultra SP-L, Catazyme® 25L, and Novozym® 960; or 2) fermentation with microorganisms, namely Aureobasidium pullulans CCY 27.1.94 and Aspergillus ibericus MUM 03.49. Under optimal conditions, 86±1g/L of sucrose was extracted from carob pulp using a pulp:water ratio of 1:3 (w/v) at 46.1°C for 132min. The enzyme blend Novozym® 960 produced the best results yielding 0.423±0.013 gFOS/ginitial sucrose, with a purity of 29.6±0.3 (w/w) after 45min of reaction. After enriching the carob pulp extract with sucrose, the yield increased to 0.496±0.005 gFOS/ginitial sucrose. When using A. ibericus a production yield of 0.347±0.003 was achieved in a carob pulp medium, and 0.454±0.003 gFOS/ginitial sucrose in a sucrose-enriched medium. Enrichment with aguamiel, a low-cost substrate supporting a more sustainable process, resulted in a prebiotic yield of 0.422±0.007 gFOS/ginitial sucrose. The carob pulp extract exhibited significant antioxidant activity, with 72.1±0.2mol TEq/g DW by the FRAP assay and 5.35±0.05g/mL by ABTS, along with high phenolic (8.57±0.04mg GAEq/g DW) and flavonoid (2.74±0.02mg CEq/g DW) contents. The treatment with Novozym® 960 enhanced the release of bioactive compounds, further increasing antioxidant activity. Conversely, fungal fermentation transformed or metabolized these phytochemicals, resulting in reduced antioxidant activity. The produced FOS exhibited notable resistance to the harsh conditions of gastro-intestinal digestion, with less than 10% undergoing hydrolysis. Carob pulp and aguamiel have shown great promise as alternatives to synthetic media for producing functional foods enriched with prebiotic FOS, phenolic acids, and flavonoids. This clean-label, cost-effective process enhances the nutritional value and functionality of the final product, providing prebiotic, antioxidant, anti-inflammatory, and anti-carcinogenic benefits.